Reimagining New Socio-Technical Economics Through the Application of Distributed Ledger Technologies - Manski, Sarah; Bauwens, Michel (Frontiers in Blockchain, 2020)
Distributed ledger technology (DLT) is increasingly proposed as a powerful tool to address the social and ecological challenges in the Global South. DLTs are opening up possible futures, one of which is a wave of infrastructure decentralization with common-centric and cosmo-local production. Shared logistics and supply chains for a circular economy, with collaborative and networked “flow” accounting allow the integration of contributive logics as well as the integration of social and ecological externalities, including practical knowledge on resource use limitations linked to planetary boundaries, as an integral part of ecosystems of productive collaboration. Indeed, DLTs remove the need for central intermediaries to validate transaction between parties, who instead place their trust in the encrypted, disintermediated system software. DLTs can be designed as a new unencloseable (non-commodifiable) medium of communication, which could lead to radically new forms of cooperation, organization, and governance. Yet these revolutionary possibilities will not be realized unless technologists consciously and strategically design systems redistributing sovereignty from elites to the people in financial, service, and national infrastructures. This paper concludes with a critical examination of the application of DLT in Puerto Rico and how DLTs could alter the production and exchange of “value” in service of a global popular sovereignty.